Evaluation of Ultrasonographic Findings in Patients with Knee Osteoarthritis: Correlations with Western Ontario and McMaster Universities Osteoarthritis Indexes - Anari, Hasan; Enteshari-moghaddam, Afsaneh; Amani, Firouz; Roshki, Kousar (Archives of Advances in Biosciences, 2022)
Introduction: Osteoarthritis is the most common chronic joint disease that affects both the elderly and the middle-aged people. This disease is the most common cause of limitation for the elderly and middle-aged people in daily activities significantly affecting the quality of their lives. The aim of this study was to evaluate the ultrasonographic findings in patients with knee osteoarthritis and its correlation with Western Ontario and McMaster Universities Osteoarthritis Indexes (WOMAC). Materials and Methods: In this cross-sectional study, patients with knee osteoarthritis, who were referred to the rheumatology clinic of Imam Hospital from April 2020 to June 2021, were evaluated by radiographic and laboratory assessment. Laboratory tests included Rheumatoid Factor (RF), Anti-Cyclic Citrullinated Peptide (Anti-CCP), Antinuclear Antibodies (ANA), Erythrocyte Sedimentation Ratio (ESR) and C-Reactive Protein (CRP); patients with positive inflammatory and serological tests were excluded from the study. Then, patients with osteoarthritis were visited by a radiologist for ultrasound findings and underwent ultrasound. In addition, the WOMAC questionnaire was administered at the same time. Results: 138 patients over 40 years old and 85.5% of whom being female were studied. The joint dryness score was significantly higher in patients with left synovial effusion (4.04 vs. 2.51; p = 0.001). In patients with right synovial hypertrophy, the mean overall score of WOMAC and its sub-branches was significantly higher (61.26 vs. 47.80; p = 0.001); also, mean joint dryness score in patients with left synovial hypertrophy is higher (4.15 vs. 3.17; p= 0.017). Conclusion: The results of the present study showed that in terms of synovial inflammation, which includes hypertrophy and synovial effusion, there is a direct relationship with patients’ WOMAC score, since ultrasound modality is non-invasive and available everywhere; moreover, the cheapness of this modality makes it possible to follow-up patients with osteoarthritis. This modality is also reliable in assessing synovial changes, but more accuracy is needed in assessing cases such as osteophyte.